Biodiversity variability of the ground beetle assemblages (Сoleoptera, Сarabidae) of a peat bog during anthropogenic transformation of their habitats - Sushko, Gennadi; Novikova, Yulia (Journal of the Belarusian State University. Ecology, 2023)
The presented research demonstrated the features of the variability of the biodiversity of the carabid assemblages in the peat bog with the different degrees of transformation in the Belarusian Lake District. The material was collected using pitfall traps in a peat bog, part of which was drained by a network of reclamation canals. The studies were carried out on an intact site (control) with specialized peat bog vegetation and on three sites of different degrees of transformation: a site with a partially disturbed sphagnum cover, peat fields with a removed sphagnum cover (open peat), and drained sites with a removedsphagnum mat covered with trees and shrubs. Differentiation of α- and β-diversity in areas of different degrees of anthropogenic transformation was revealed. The average number of species (χ2 = 10.72, p = 0.01) and individuals (F = 57.54, p = 0.001) in the samples differed significantly. If the sphagnum cover was disturbed or completely removed, the number of species decreases as compared to the control biotopes. Whereas during the formation of tree and bush cover, on the contrary, species richness increases. The average number of individuals decreases, except for sites with partially disturbed sphagnum cover. With an increase in anthropogenic transformation, species diversity and evenness was higher compared to the control (H’ = 1.54 ± 0.05, J’ = 0.42 ± 0.03) and reach a maximum in sites with woody vegetation (H’ = 2.48 ± 0.38, J’ = 0.97 ± 0.11). The values of the Shannon diversity index (χ2 = 14.57, p = 0.002) and the Pielou evenness index (F = 18.44, p = 0.001) differed significantly in all studied habitats. The analysis of β-diversity demonstrated significant differences in the species composition of ground beetle assemblages in sites with different degrees of transformation (ANOSIM; R = 0.90, p = 0.0001). The species composition and dominance structure of ground beetle assemblages undergo the greatest changes when the sphagnum cover is completely removed. At the same time, the composition of the group of dominants is significantly expanding. Specialized raised bog species Agonum ericeti (Panzer, 1809), Pterostichus diligens (Sturm, 1824) and P. rhaeticus Heer, 1838 were replaced by open space dwellers and eurytopic species such as Cicindela sylvatica Linnaeus, 1758, Poecilus cupreus (Linnaeus, 1758), P. versicolor (Sturm, 1824), Agonum sexpunctatum (Linnaeus, 1758), Harpalus latus (Linnaeus, 1758).
Keywords: α- and β-diversity; ground beetles; anthropogenic impact